Strategic Intervention for Selected Deviant English Phrases at a rural University - Nephawe, Farisani Thomas (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Professionalism in English phrases is an indispensable tool for the enhancement of fluency and accuracy in communication. However, English second language learners face redundancy challenges apropos an effective use of phrases. The research investigated strategic intervention for selected deviant English phrases at the University of Venda. A quantitative approach was adopted because data could be analysed mathematically and statistically. Using probability sampling, 35 Level Three English students registered in the 2022 academic year at this university were selected to participate in this research. Further, a convenience technique was employed to select the respondents who were readily approachable and had been studying English for more than twelve years. A pre-test study was conducted on the respondents who were not part of the target group to plan and modify the main research. After a treatment process was followed, the research revealed that respondents were incompetent in the use of English phrases. Nonetheless, post-test results established that respondents performed preternaturally after the utilisation of the ‘language shadowing methods’. Frequent practice in the use of this technique, therefore, cannot be ignored if one wishes to improve not only the art of public oration but also the image of the person's academic literacy.